Integrative analysis of grapevine (Vitis vinifera L) transcriptome reveals regulatory network for Chardonnay quality formation - Fu, Guangqing; Ren, Yanhua; Kang, Jun; Wang, Bo; Zhang, Junxiang; Fang, Jinggui; Wu, Weimin (Frontiers in Nutrition, 2023)
Fruit shape, soluble sugar, total phenols and anthocyanins are important components that determine unique fruit quality and consumer preference. However, the transcriptomics and underlying regulatory networks that regulate overall quality formation during fruit development and ripening remain largely unknown in most fruit species. In this study, the quality-related transcriptome data of 3 fruit development and maturity stages of Chardonnay cultivars in 6 ecological regions were integrated. Using this dataset, we constructed a complex regulatory network that can identify key structural genes and transcription factors that regulate fruit shape, soluble sugars, total phenols, and anthocyanins in grapes. Overall, in addition to providing new insights into quality regulation during grape fruit development and ripening, our findings lay the foundation for the improvement of grape quality.